Waste to Energy: Calorific Improvement of Municipal Solid Waste through Biodrying - Zaman Badrus (Sciendo, 2021)
Municipal solid waste (MSW) is an energy resource with sufficient energy/calorific value, making it a suitable substitute for fuel. This study investigated the effect of air flow rate on the MSW calorific value, the hemicellulose content, and the MSW degradation rate in a biodrying process. Four biodrying reactors equipped with flowrate and temperature recorders were used in the study. The air flow rate was varied as follows: 0 L/min/kg, 2 L/min/kg, 4 L/min/kg, and 6 L/min/kg, corresponding to reactors R1, R2, R3, and R4, respectively. The calorific value, water content, hemicellulose content, organic C content, and total N were measured on day 1, day 15, and day 30. The results showed that the biodrying process could increase the calorific value by 55.3 %, whereas the control reactor could increase the calorific value by only 4.7 %. The highest calorific value was 17.63 MJ/kg, at an air flow rate of 4 L/min/kg. The air flow rate had a significant effect on increasing the calorific value (sig.<0.05). The highest temperature in the biodrying process was 41 °C. The final MSW moisture content was 27.28 %, resulting from R4. According to the statistical test results, the air flow rate had a significant influence on the water content parameters. Hemicellulose degradation due to air flow rate reached 80–85 %. The air flow rate did not significantly influence the hemicellulose degradation (sig.>0.05). The biodrying process is the suitable method to increase the calorific value of MSW while reducing its water content; thus, the process promotes the realization of waste to energy as refuse-derived fuel.